Inversion Method of Formation Water Salinity in Hydrocarbon-Bearing Sandstone Based on Spontaneous Potential - ZHANG Jiansheng; LU Yunlong; QI Yi; KANG Nan (Cejing jishu)
The formation water salinity is an important reservoir parameter, which is also the basis for reservoir fine evaluation. When the reservoir contains hydrocarbons, the abnormal amplitude of the spontaneous potential curve decreases, which affects the accuracy of inverting the formation water salinity. Based on experimental data from publicly published articles, the relationship between water saturation, formation water salinity, mud filtrate salinity, and spontaneous potential reduction in pure sandstone reservoirs is quantitatively characterized. This relationship is combined with a saturation model to construct an inversion model for water salinity in hydrocarbon bearing sandstone reservoirs based on spontaneous potential curves. The inversion model is applied in the target well and an experiment of measuring bound water salinity is carried out to verify the inverse method. It shows that the inversion results are basically consistent with the experimental results. The method accurately characterizes the suppression effect of hydrocarbons on the spontaneous potential curve, and can accurately calculate the formation water salinity, providing a basis for fluid identification and reservoir evaluation.